A Technique to Minimize Aerosolization During Percutaneous Tracheostomy in COVID-19 Patients. Issue 8 (August 2020) - Betancourt-Ramirez, Alejandro; Yelon, Jay A.; Boland, Paul; Amaturo, Michael
Background: The SARS-CoV-2 pandemic has caused respiratory failure in many patients. With no effective treatment or vaccine, prolonged mechanical ventilation is common in survivors. Timing and performance of tracheostomy, for both patient and surgical team safety, remains a question. Here within, we report our experience with percutaneous dilatational tracheostomy with modification to minimize aerosolization. Methods: A modified percutaneous dilatational tracheostomy technique is described. The technique was performed on 10 patients in the surgical intensive care unit. Results: Ten patients underwent percutaneous dilatational tracheostomy. There were 7 males, and the average age for the group was 60.8 years. The average number of ventilator days before the operation was 26.3. All procedures were successful, and no patient had any procedure-related complications. Conclusions: The procedure described was successful in our patient population. We believe that this approach is safe for patients with coronavirus disease 2019 and limits aerosolization during the operation. Level of evidence: Level IV, case series.